Isolation of high-quality dna in 16 aromatic and medicinal colombian species using silica-based extraction columns (2011)
Aromatic and medicinal plant species are a valuable resource for research and development of pharmaceutical, cosmetic, crop protection and nutritional agents, due to the high amount of bioactive phytochemicals that they contain. However, these compounds are a major obstacle in the isolation of high-quality DNA suitable for genetic analyses. In this paper, we report a protocol that optimizes the use of the cationic detergent CTAB and the reductant β-mercaptoethanol in cell lysis. The elimination of plant secondary metabolites such as polysaccharides and polyphenols, that typically co-isolate with DNA, was achieved using the chemical denaturing properties of the guanidinium cation, which together with the adsorbent chemical specificity of the silica, resulted in the purification of high-quality DNA suitable for digestion with restriction enzymes and optimal for PCR amplification of AFLP-type molecular markers. This protocol was evaluated on 16 Colombian aromatic and medicinal plant species promising for their essential oils. The results allow suggesting that this procedure might be appropriate for other species, tissues and sample types recalcitrant to DNA extraction.